BATANG STEAM POWER PLANT, THE STRUGGLE OF INTERESTS BETWEEN THE CENTRAL GOVERNMENT AND THE LOCAL COMMUNITY - Ery Agus Priyono (Diponegoro Law Review, 2017)
The electricity power crisis will hit the island of Java 2018 due to growth in electrical load continues to increase with growth per year to reach about nine percent. Steam Power Plant in Batang District has become the main hope in overcoming the electricity power crisis, especially in Java and Bali.Construction of the power plant in the district of Batang situated on land and at sea. There is no problem with land area because it has in accordance with the Spatial Batang District regulation, but the position at sea It crash to Government Law (PP) no. 26 year 2008 of National Spatial Plan. It triggers a conflict between central and local governments on the one hand with the local community on the other hand. Resolution of the conflict can not be patterned positivistic application of the law but the application of laws that are pluralism that enables a win-win solution.